PERAN SERTA KOMITE MADRASAH DALAM UPAYA MENINGKATKAN MUTU PENDIDIKAN (Penelitian di Madrasah Aliyah Swasta GUPPI Al Barkah Desa Sukajadi Kecamatan Sadananya Kabupaten Ciamis) - Suhendar, Suhendar; Nurjanah, Hj.; Hayatunnufus, Alifa Baiduri (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2017)
This study aims to examine and analyze the role of the GUPPI Al-Barkah Private Madrasah Aliyah committee in improving the quality of education in the Madrasah. The results of the study can be summarized as follows: 1) The role of the madrasah committee in giving consideration to improve the quality of education in the Private Aliyah Madrasah GUPPI Al Barkah is realized in the form of giving input to the education management process and learning process; giving consideration to the provision and use of facilities and infrastructure needed and the use and utilization of madrasah budgets; 2) The support provided by the madrasah committee to improve the quality of education in the Private Aliyah Madrasah GUPPI Al Barkah by monitoring the condition of human resources and infrastructure. 3) the madrasa committee in carrying out its role as a controller in improving the quality of education in the Private Aliyah Madrasah GUPPI Al Barkah is carried out in the form of supervision of all educational activities in madrasas; 4) the role of the committee as a mediator is realized as a liaison and container of aspirations from the community.